Naposo Nauli Bulung (NNB) Based Health Cadre Education Model on Reproductive Health Behavior of Adolescent Girls - Batubara, Rini Amalia; Hasibuan, Ahmad Safii; Pohan, Sakinah Yusro (Jurnal Kesehatan - STIKes Prima Nusantara, 2024)
Background:  Adolescents are at high risk of being exposed to reproductive health problems, so the opportunity to access information and receive sexual and reproductive health education is important for adolescents.Objective: The aim is to assess the influence of Naposo Nauli Bulung-based health cadre education model on the reproductive health behavior of female adolescents.Method: The type of research is an experiment with a research design quasi eksperiment pre-post with control design. Pre-test and post-test using a questionnaire. Sampling used Non Probability Samples with purposive sampling technique. The samples taken were 60 young women.Result:  There were significant differences between the treatment groups in the knowledge, attitudes and actions of young women. Knowledge and treatment groups on adolescent knowledge and attitudes. Knowledge p=0.000, attitude p=0.000, and action p=0.000.Conclusion: Providing interventions through Providing health education based on local wisdom Naposo Nauli Bulung (NNB) is one of the effective health education methods used to increase the knowledge, attitudes and actions of teenagers.